Funkcja doskonaląca (prakseologiczna) zasad prawnych zawartych w k.p.a. w zakresie wydawania decyzji administracyjnej: [Praxeological function of principles included in the administrative code in the area of administrative decision-making processes] (Studia Prawnicze / The Legal Studies, 2011)
Zasady ogólne (podstawowe) postępowania administracyjnego zawarte są w rozdziale 2 działu I k.p.a. Nazwy ich zostały określone przez doktrynę. Zalicza się do nich między innymi zasady: 1) legalności, 2) praworządności, 3) prawdy obiektywnej (materialnej), 4) uwzględniania interesu społecznego i słusznego interesu obywateli, 5) budzenia zaufania obywateli do organów administracji publicznej, 6) obowiązku organu udzielania obywatelowi informacji faktycznej i prawnej, 7) czynnego udziału strony w postępowaniu, 8) przekonywania, 9) szybkości postępowania, 10) ugodowego załatwienia sprawy, 11) pisemności (dokument papierowy i elektroniczny), 12) dwuinstancyjności, 13) zaskarżalności decyzji do sądu.Wszystkie wymienione zasady postępowania administracyjnego w mniejszym lub większym stopniu mają wpływ na procedurę wydawania decyzji administracyjnej w tzw. postępowaniu jurysdykcyjnym (orzekającym). Ponieważ są wspólne dla całości postępowania administracyjnego, stosuje się je w stosunku do wszystkich przepisów kodeksu, we wszystkich stadiach postępowania. Development (praxeological) function of legal provisions included in the Administrative Code in the area of administrative decision-making processes Administrative Code with its legal provisions of administrative proceeding (Articles 6-16) is considered to perform various functions, which have been reported in the published literature, such as efficiency, functionality and capableness in the activities of public administration authorities. Even though many functions of administrative procedures have been abundantly depicted in the published literature so far no author has referred to its developmental and praxeological function in the process of administrative decision making which has been presented in this study. It seems that praxeological and developmental function of the administrative procedures in the process of administrative decision making is crucial for the proper functioning of the public administration bodies i.e. authorities of the first and second administrative level, supervisory authorities and administrative judiciaries. In order to substantiate the developmental and praxeological function I have presented certain indicators (criteria) of two complementary requirements i.e. legitimacy and efficiency which are based on the procedural standards of administrative law and legal doctrine associated with administrative decisionmaking. Efficiency, as one of the requirements mentioned above, is described in my study by several indicators such as time (swiftness), resourcefulness (activeness) and method (form) of communication in the recognition process. Another aspect of the efficiency requirement is the economical aspect which has been described as productivity and thriftiness in the administrative processes. The third and most important criterion of efficient administration has been linked with the legitimacy and validity of the process and the way of its interpreting has been explained in my work. In the final stage of my study I have explained two roles the developmental function plays within the scope of administrative decision making i.e. its preventive role which is aimed at eliminating potential causes of undesired events that might occur in the administration process as well as its corrective role which allows the administrator to eliminate the symptoms of the actions which have occurred in the fulfilment of administrative duties. In the summary section of my study I have emphasised that the developmental function of the legal provisions of the administrative code can be a useful tool in the improvement of the quality of services provided by public administration authorities for the citizens of its country by making administrative decisions.